2016
DOI: 10.1038/labinvest.2015.140
|View full text |Cite
|
Sign up to set email alerts
|

WNT signaling in glioblastoma and therapeutic opportunities

Abstract: WNTs and their downstream effectors regulate proliferation, death, and migration and cell fate decision. Deregulation of WNT signaling is associated with various cancers including GBM, which is the most malignant primary brain cancer. In this review, we will summarize the experimental evidence supporting oncogenic roles of WNT signaling in GBM and discuss current progress in the targeting of WNT signaling as an anti-cancer approach. In particular, we will focus on (1) genetic and epigenetic alterations that le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
191
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(198 citation statements)
references
References 162 publications
(191 reference statements)
5
191
0
2
Order By: Relevance
“…Findings on Wnt5a roles and functions in these tumors are restricted to the observed increased motility in cultured cell lines (25,27). Recently, however, it has been shown that the enhanced migration caused in hGBMs by reduced Wnt inhibitor 1 activity is mediated by Wnt5a (48).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings on Wnt5a roles and functions in these tumors are restricted to the observed increased motility in cultured cell lines (25,27). Recently, however, it has been shown that the enhanced migration caused in hGBMs by reduced Wnt inhibitor 1 activity is mediated by Wnt5a (48).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that Wnt5a is overexpressed in high-grade gliomas, but the role for Wnt5a in regulating proliferation and migration in gliomas has only been demonstrated, in a few cell lines, in vitro (23)(24)(25)(26)(27). Here, we explore whether Wnt5a can function as a master regulator of the invasive capacity of hGBMs.…”
Section: Introductionmentioning
confidence: 94%
“…Epigenetic changes including promoter hypermethylation reduce the expression of these inhibitors and, as a consequence, there is a hyperactivation of WNT/FZD signalling. In turn, this effect yields to β-cat activation in GBM cells and contributes to tumor progression (reviewed in [14]). …”
Section: Comment and Discussionmentioning
confidence: 99%
“…Комбинированная гипорегуляция SFRP1 одновременно с гиперрегуляцией SFRP4 и FZD7 значительно снижала медиану выживаемости пациентов с глиомами [41]. Эпигенетические изменения играют бóльшую роль в активации Wnt-сигналинга, чем геномные мутации [42].…”
Section: Wnt-сигналингunclassified